2022
DOI: 10.3389/fpubh.2022.821703
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behavior in University Students–The Role of Gender, Age, Field of Study, Targeted Degree, and Study Semester

Abstract: BackgroundPhysical inactivity and sedentary behavior are modifiable risk factors for an unhealthy lifestyle in university students. The aim of this study was to identify subgroups among German university students with an increased risk for unhealthy behavior. For this purpose, differences in physical activity and sedentary behavior with respect to sociodemographic and study related factors were examined.MethodsA total of 4,351 students participated in an online survey. The amount of physical activity (metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 61 publications
1
15
0
4
Order By: Relevance
“…Sedentary lifestyles can negatively impact students’ health, increasing the risk of non-communicable diseases, such as obesity, heart disease and diabetes, and poor academic performance ( 10 , 23 ). Numerous studies have confirmed the importance of physical exercise in promoting health, constituting an essential component in global intervention strategies, integrating health policies in developed and developing countries ( 10 , 21 , 57 , 58 ). In the current study, the results indicate less physical activity and align with trends observed in previous studies ( 10 , 19–21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary lifestyles can negatively impact students’ health, increasing the risk of non-communicable diseases, such as obesity, heart disease and diabetes, and poor academic performance ( 10 , 23 ). Numerous studies have confirmed the importance of physical exercise in promoting health, constituting an essential component in global intervention strategies, integrating health policies in developed and developing countries ( 10 , 21 , 57 , 58 ). In the current study, the results indicate less physical activity and align with trends observed in previous studies ( 10 , 19–21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary behaviors in the presented study expressed as a total sitting component (min per week) were worse than other Polish student populations [ 48 ] and Scandinavian students. Some studies showed a significant difference between male and female students regarding PA but not regarding sedentary behaviors [ 53 ]. The presented study is in partial agreement with Edelmann et al, suggesting that there are no sex differences in total PA and total sitting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…De Souza et al [9] observed a prevalence of physical inactivity of 67% and 34% in medicine and physical education students, respectively. Similarly, other studies have also reported insufficient physical activity levels in undergraduate students and they have been shown to be associated with health outcomes such as depression and daytime sleepiness [12][13][14]. In this scenario, it is reasonable to speculate that physically inactive undergraduate students may show mental disorders and, consequently, poor quality of life.…”
Section: Introductionmentioning
confidence: 89%